A Cause Without Rebels? Om emancipationens forsvundne subjekt - Holm, Andreas Beck (Slagmark - Tidsskrift for idéhistorie, 2015)
It was Marx who first formulated what later became known as the idea of the working class as an ‘emancipatory subject’. In his view, the workers alone were able to orchestrate a revolution that would put an end to capitalism. The purpose of this paper is to show that this line of thought is ideological by Marx’s own standards, and that while the working class never constituted the coherent political subject that Marx wanted it to become, its non-existence produced distinct theoretical effects not just in his work, but also (taking Lukács as an example) in the Marxist tradition. After a brief discussion of the different criticisms of the idea of the working class as emancipatory subject put forward by Hardt, Negri, Laclau, and Mouffe, an attempt is made to demonstrate how Althusser’s structural approach is better suited to formulate an alternative to the traditional view. Finally it is argued that this alternative stays within a general Marxist framework.